Legal Protection for Copyright of Collaborative Content on Social Media: The Role and Strength of Treaty Law in Determining Ownership and Use - Anggo Doyoharjo; FX. Hastowo Broto Laksito; Kesya Zhalibina Sunarto (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of social media has given rise to a new form of digital creative work thru collaboration between influencers and brands, known as brand collaboration. This phenomenon poses new challenges to the copyright legal system, particularly regarding the determination of ownership and legal protection of collaboratively generated content. This research aims to analyze how legal protection for social media content copyright is applied within the context of digital cooperation, and to what extent agreements play a role in determining the ownership and utilization of economic rights to such works. The research method used is normative juridical with a conceptual and legislative approach, which examines the provisions in Law Number 28 of 2014 concerning Copyright, contract related regulations, and international principles in the Berne Convention and the WIPO Copyright Treaty. The research results indicate that legal protection for collaborative content on social media is not yet optimal due to weak legal awareness and minimal contractual regulation between the parties. Written agreements have proven to play a strategic role in providing legal certainty over moral and economic rights, while also serving as a tool to prevent disputes and misuse of content. Therefore, it is necessary to develop more explicit digital collaboration contract guidelines and provide legal education for creative industry players so that copyright protection in Indonesia can be effective, adaptable, and equitable in the digital economy era.